Village Financial Management Model in Jayapura City, Papua Province - Kristhina R.I. Luluporo; Agustinus Fatem; Yosephina Ohoiwutun; Septinus Saa (Formosa Journal of Science and Technology, 2023)
This study will also provide a description and contribution of thought by formulating a village financial management model, as well as an alternative reference for solving problems faced by village governments in making decisions, formulating and establishing policies, preparing skilled and competent human resources as the main driver in increasing empowerment and participation of village communities. The method used is a qualitative approach, data is obtained from observation, interviews and documentation. The results of the study show that village financial management in the Jayapura City government area still faces a number of obstacles, such as problems with apparatus resource capacity, internet networks, including the lack of evaluation at the village level. Nevertheless, village financial management in Jayapura City is supported by traditional leadership (ondoafi). The results of this study also formulate an effective village financial management model, of course based on village fund management issues or problems which are then provided with solutions.